The effect of organisational culture on students' cognitive, skill-based, and affective learning outcomes in higher education in Saudi Arabia [El efecto de la cultura organizacional en los resultados de aprendizaje cognitivo, basado en habilidades y afectivo de los estudiantes en la educación superior en Arabia Saudita] - Radwan, Omaymah; Razak, Ahmad Zabidi Abdul (Universidad del Zulia, 2019)
The current study aimed to analyze the effect of organizational culture on students cognitive, skill-based and affective learning outcomes in Saudi higher education institutions. It has been conducted a quantitative research methodology by distributing questionnaires which contained 95 items to faculty members at two Saudi higher education institutions. 496 responses were further analysed using the SPSS (V23) and PLS-SEM. Results indicated that organisational culture has a direct and significant positive effect on students’ cognitive, skill-based, and affective learning outcomes in the context of Saudi higher education. The present study has a potential to reflect positively on the Ministry of Education, academic leaders, as well as support the higher education institutions. © 2019, Universidad del Zulia. All rights reserved.